KEGAGALAN RENCANA AKSI SIAK KABUPATEN HIJAU DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN TAHUN 2018-2019 - Ningsih, Risma Lutfia Wahyu; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The forest fire problem is a global problem. Forest and land fires have detrimental impacts on the environment, social and economy. Forest and land fires that occur on peatlands are much more difficult to handle than those that occur on high-level mineral soil forests. Siak Regent Regulation Number 22 of 2018 concerning the Green Siak Initiative is a preventive effort by the District Government in preventing forest and land fires. However, this policy has not been able to solve the problem of forest and land fires in Siak Regency. Fires occur every year in Siak District, and they even increase after the Siak Hijau Program was published.This study aims to determine how the implementation of the action plan for forest and land fire prevention in the Siak District Railway according to the Siak Hijau Roadmap. The research method used in this research is research with qualitative analysis.The results of this study indicate that the implementation of the Green Siak Initiative for the prevention of forest and land fires in 2019-2020, based on the spectrum of policy failures McConnell (2015) at the stage as a program or policy implementation shows an immediate failure. One of the causes of the failure of the Siak Hijau policy includes the Action Plan for the prevention of forest and land fires in accordance with the Siak Hijau Roadmap itself in Siak Regency which does not have a binding legal base, it does not enter the Siak Hijau budget into the Siak Regency Regional Budget (APBD). Keywords: Siak Hijau, District Government, Forest and Land Fires